2016
DOI: 10.1021/acs.bioconjchem.6b00519
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-Targeted Photodynamic Therapy with a Galactodendritic Chlorin to Enhance Cell Death in Resistant Bladder Cancer Cells

Abstract: Here, we report the rational design of a new third-generation photosensitizer (PS), a chlorin conjugated with galactodendritic units, ChlGal, to improve the effectiveness of bladder cancer treatment. ChlGal shows better photochemical and photophysical properties than a recently reported homologous porphyrin, PorGal. In addition to inheriting excellent photostability, the ability to generate singlet oxygen, and the ability to interact with the proteins galectin-1 and human serum albumin (HSA), ChlGal exhibits h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 41 publications
1
48
0
Order By: Relevance
“…There is growing interest in the development of porphyrinoids conjugated with sugars such as glucose and galactose as new PSs for the PDT of cancer [6, 10, 11, 13, 35, 36]. Galectin-1 and GLUT1 are glyco-binding proteins overexpressed in cancer cells [37, 38] that play a key role in the uptake and photo-toxicity of with galactose- and glucose- porphyrin conjugates [11, 39, 40].…”
Section: Resultsmentioning
confidence: 99%
“…There is growing interest in the development of porphyrinoids conjugated with sugars such as glucose and galactose as new PSs for the PDT of cancer [6, 10, 11, 13, 35, 36]. Galectin-1 and GLUT1 are glyco-binding proteins overexpressed in cancer cells [37, 38] that play a key role in the uptake and photo-toxicity of with galactose- and glucose- porphyrin conjugates [11, 39, 40].…”
Section: Resultsmentioning
confidence: 99%
“…[5] Although PDT has numerous advantages, its broader acceptance in clinical practice is restricted mainly due to the limited penetration depth of the visible light through tissues, lack of cancer cell selectivity and reduced level of oxygen in most of the solid tumors (tissue hypoxia). [8] On the other side, subcellular localization of PSs particularly to the MT can address the problems related to hypoxia [9] and enhance the PDT effect [10][11][12][13] since MT play important roles in cell respiration, oxygen metabolism and apoptosis signalling. [6,7] In this context, organelletargeted and red/near-IR absorbing PSs are highly promising.…”
Section: Introductionmentioning
confidence: 99%
“…GOMES, MARIA G.P.M.S. NEVES and JOSÉ A.S. CAVALEIRO Considering these promising works, in 2016 it was reported the synthesis of the chlorin derivative Chl-Gal 8 46 also conjugated with galactodendritic units (Figure 36) (Pereira et al 2016a). The synthetic approach was also based on the nucleophilic substitution by the galacto-dendridic unit 43 of the p-fluorine atoms of the chlorin ChlF 20 ; this chlorin was obtained from TPPF 20 through a 1,3-dipolar cycloaddition process as it was previously described by Cavaleiro´s group (Silva et al 1999(Silva et al , 2005.…”
mentioning
confidence: 99%
“…The synthetic approach was also based on the nucleophilic substitution by the galacto-dendridic unit 43 of the p-fluorine atoms of the chlorin ChlF 20 ; this chlorin was obtained from TPPF 20 through a 1,3-dipolar cycloaddition process as it was previously described by Cavaleiro´s group (Silva et al 1999(Silva et al , 2005. The results showed that this chlorin has excellent photostability, high ability to generate singlet oxygen and to interact with the proteins galectin-1 and human serum albumin (HSA) (Pereira et al 2016a). Besides the Chl-Gal 8 46 exhibits high absorption in the red region of the electromagnetic spectrum where tissue light penetration is rather high, which is an important requirement for PDT (Senge and Brandt 2011, Lu et al 2015, Agostinis et al 2011.…”
mentioning
confidence: 99%
See 1 more Smart Citation